Polycentric Defense. - COYNE, CHRISTOPHER J.; GOODMAN, NATHAN P. (Independent Review)
The article offers information on Polycentric Defense in the U.S. It mentions taking "the nation" as the relevant unit of analysis, economists model defense as a good that is jointly consumed, nonexcludable, and nonrival over a significant geographic space; and orthodox treatment of defense as a pure public good that must be provided by a centralized state suffers from three key issues.